(untitled) (Iraqi National Journal of Earth Science (INJES), 2025)
2400 m/s and Vs >1100 m/s is considered the sandstone of the Mukdadiya Formation. According to the information provided, the 3rd and 4th layers are appropriate for the engineering project. The resulting geotechnical properties in the area can be used for the preliminary foundation design of any engineering construction.]]>